The efficacy of the Djibouti code of conduct in suppressing piracy and armed robbery against ships in the Western Indian Ocean and the Gulf of Aden: An appraisal - Win, Kyaw Hla; Ansari, Abdul Haseeb; Masum, Ahmad (The American Society of International Law, 2016)
The Horn of Africa marked as the hottest piracy spot of the world during 2008- 2011. Nevertheless, after the implementation of the Code of Conduct concerning the Repression of Piracy and Armed Robbery against Ships in the Western Indian Ocean and the Gulf of Aden (Djibouti Code of Conduct), the region has been experiencing lesser incidents and there has been a sharp decrease during the past four consecutive years, i.e. 2012, 2013, 2014 and 2015. Accordingly, this paper intends to evaluate the efficacy of the Djibouti Code of Conduct in suppressing piracy and armed robbery in the Western Indian Ocean and the Gulf of Aden. In this paper, authors propose that the current tempo of counter piracy measures have to be maintained by the Participants and other interested States through their continuous physical presence in the region. It is further suggested to widen the scope of maritime crimes under the Djibouti Code of Conduct and include maritime terrorism. It is preferable to remove the two ships requirement from the piracy definition and include the phrase “Exclusive Economic Zone of a State Party” into the definition of armed robbery against ships. All Participants are advised to allow the hot pursuit in their territorial waters in arresting or seizing culprits and cooperate with the requesting Participant. All ships passing through the waters in the region are recommended to notify the flag state, the nearest national focal point of a Participant and the information exchange centre when any incident takes place. All information exchange centres and national focal points should also be well equipped with advanced technologies.